PELAKSANAAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI TK BIAS YOGYAKARTA - Yuli Tri Andini; Melia Dwi Widayanti (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2020)
Covid-19 cases was first reported in March 2020. To protect their citizen, the goverment made some regulation and one of them is school from home. TK BIAS Giwangan is one of kindergarten that apply school from home since the regulation started. In this research, we would like to get the information about how TK BIAS GIWANGAN run their school from home programme. We used qualitative approach with observation and interview method. The result is TK BIAS GIWANGAN held a school from home programme. The fundamental reason for the teacher choosing learning theme is the easiness, simplicity, and interesting. They used Whatsapp and Zoom as the main application to held learning process. Assesment and evaluation process was held by observing chldren’s response and behaviour while learning by Zoom and they also did home visit to facilitate children that cannot join the class.